2023
DOI: 10.3389/fchem.2023.1114434
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induced by berberine-based mitochondria-targeted low temperature photothermal therapy

Abstract: Introduction: Mitochondria-targeted low-temperature photothermal therapy (LPTT) is a promising strategy that could maximize anticancer effects and overcome tumor thermal resistance. However, the successful synthesis of mitochondria-targeted nanodrug delivery system for LPTT still faces diverse challenges, such as laborious preparations processes, low drug-loading, and significant systemic toxicity from the carriers.Methods: In this study, we used the tumor-targeting folic acid (FA) and mitochondria-targeting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Their single-dose NIR irradiation (for 5 min at 808 nm) inhibited ATP synthesis and disturbed mitochondrial function and the energy supply in cancer cells. Moreover, Hu et al [ 85 ] have observed that cancer cells treated with GO-based nanocomposites in combination with a low-temperature PTT exhibited mitochondrial depolarization, depletion of ATP, and substantial ROS generation, leading to mitochondrial-associated apoptosis. The formation of intracellular ROS triggered by GO after NIR irradiation is also demonstrated in mouse melanoma tumors by Kalluru et al [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their single-dose NIR irradiation (for 5 min at 808 nm) inhibited ATP synthesis and disturbed mitochondrial function and the energy supply in cancer cells. Moreover, Hu et al [ 85 ] have observed that cancer cells treated with GO-based nanocomposites in combination with a low-temperature PTT exhibited mitochondrial depolarization, depletion of ATP, and substantial ROS generation, leading to mitochondrial-associated apoptosis. The formation of intracellular ROS triggered by GO after NIR irradiation is also demonstrated in mouse melanoma tumors by Kalluru et al [ 86 ].…”
Section: Resultsmentioning
confidence: 99%